Power quality improved SMPS using bridgeless isolated zeta converter for welding applications. Issue 4 (1st October 2016) - Narula, Swati; Singh, Bhim; Bhuvaneswari, G.
Abstract: A single-phase power factor corrected bridgeless isolated zeta converter is presented in this paper for arc welding power supplies. Eliminating diode bridge rectifier at the front end minimizes the conduction losses and enhances the thermal utilization of the converter switches. The converter is functioning in discontinuous conduction mode pertaining to the magnetizing inductance of the transformer to enable power factor correction inherently. A double loop controller is proposed to integrate over-current limiting capability along with regulating the DC arc welding voltage. The proposed switched mode power supply (SMPS) is designed to operate under a wide range of load and supply voltage conditions with improved input power quality (IPQ). The performance of the SMPS is simulated and the test results are evaluated on the basis of input power factor as well as total harmonic distortion of the supply current, voltage regulation and robustness to validate the viability of the proposed SMPS. A prototype of the proposed SMPS is developed and the experimental results have been obtained which establish the efficacy of the proposed bridgeless SMPS in maintaining excellent IPQ at the utility interface point.